Analisis Pengaruh Komunikasi Dan Kecerdasan Emosional TerhadapKinerja Pegawai Puskesmas Jatiroto Kabupaten Wonogiri - Utomo, Cahnadra Wisnu, Jati Waskito S.E., M.Si (2016)
This study aimed to determine the effect of communication and emotional intelligence to employee performance UPT Puskesmas Wonogiri Jatiroto. The sample in this study is the health center staff totaling 34 respondents. The sampling technique in this research is purposive sampling method. Data analysis methods used were normality test and test multiple linear regression analysis with t-test, F, and the coefficient of determination (R2). In this study the data meet for a normal distribution. Hypothesis tests showed that the variables of communication and emotional intelligence have significant influence with t respectively 2.239 and 2.465 on employee performance. In the F test showed that together communication and emotional intelligence variables significantly influence employee performance. The coefficient of determination (R2) of 0.363 indicates that employee performance can be explained by communication and emotional intelligence by 36.3%